Protocol for functional screening of CFTR-targeted genetic therapies in patient-derived organoids using DETECTOR deep-learning-based analysis - Mattijs Bulcaen; Ronald B. Liu; Kasper Gryspeert; Sam Thierie; Anabela S. Ramalho; François Vermeulen; Xavier Casadevall I Solvas; Marianne S. Carlon (STAR Protocols)
Summary: Here, we present a protocol for the rapid functional screening of gene editing and addition strategies in patient-derived organoids using the deep-learning-based tool DETECTOR (detection of targeted editing of cystic fibrosis transmembrane conductance regulator [CFTR] in organoids). We describe steps for wet-lab experiments, image acquisition, and CFTR function analysis by DETECTOR. We also detail procedures for applying pre-trained models and training custom models on new customized datasets.For complete details on the use and execution of this protocol, refer to Bulcaen et al.1 : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.